ROS 2019
DOI: 10.20455/ros.2019.835
|View full text |Cite
|
Sign up to set email alerts
|

GPx4 in Bacterial Infection and Polymicrobial Sepsis: Involvement of Ferroptosis and Pyroptosis

Abstract: While it is well known that bacterial infection is the predominant cause of sepsis, the molecular pathophysiology of this clinical syndrome remains ill-defined. In this Research Highlights article, we discuss the recent research findings regarding a protective role for glutathione peroxidase-4 (GPx4) in bacterial infection and polymicrobial sepsis via modulating ferroptosis and pyroptosis, two novel modes of regulated cell death. It is suggested that GPx4, being a requisite gateway to both ferroptosis and pyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 36 publications
4
50
1
1
Order By: Relevance
“…Mechanistically, D3T suppresses LPS-induced proinflammatory cytokine gene expression in an Nrf2-dependent manner in inflammatory cells and such suppression stems, at least partly, from D3T-mediated inhibition of the NF-κB pathway. In addition, D3T-mediated upregulation of cellular antioxidants, particularly GPx4 [9], and downregulation of cellular iron may also lead to suppression of ferroptosis and pyroptosis, two critical pathophysiological events in sepsis [27] (Figure 11).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, D3T suppresses LPS-induced proinflammatory cytokine gene expression in an Nrf2-dependent manner in inflammatory cells and such suppression stems, at least partly, from D3T-mediated inhibition of the NF-κB pathway. In addition, D3T-mediated upregulation of cellular antioxidants, particularly GPx4 [9], and downregulation of cellular iron may also lead to suppression of ferroptosis and pyroptosis, two critical pathophysiological events in sepsis [27] (Figure 11).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these studies suggest that, unlike other types of necrotic cell death, ferroptosis induction favors pathogen dissemination or virulence and not host defense. That ferroptosis might worsen the outcome of bacterial infections is also supported by a new study that showed that GPX4 deficiency in myeloid cell increases the severity of polymicrobial sepsis in mice, since GPX4 was necessary to block phospholipase C gamma 1 (PLCG1)‐mediated GSDMD activity and pyroptosis 93 . However due the recent emergence of the ferroptosis pathway and the lack of genetic tools, we currently know too little about this pathway to definitely conclude that ferroptosis cannot be protective as well.…”
Section: Programmed Cell Death During Bacterial Infectionmentioning
confidence: 98%
“…Peculiarly, ferroptosis causes irreversible alteration of mitochondrial morphology ( Twig & Shirihai, 2011 ). Furthermore, substantial evidence revealed that ferroptosis is involved in bacterial infection induced cell death and tissue damage ( Zhu et al, 2019 ). For instance, Pseudomonas aeruginosa was shown to trigger ferroptosis in host bronchial epithelium through generating lipoxygenase, that is involved in the initiation of lipid peroxidation, by oxidizing host arachidonic acid–phosphatidylethanolamines ( Dar et al, 2018 ).…”
Section: The Role Of Ferroptosismentioning
confidence: 99%